Program Layanan Bimbingan Klasikal untuk Meningkatkan Self-Control Siswa - Mukhtar Mukhtar; Syamsu Yusuf; Amin Budiamin (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2016)
This research aimed to know the effectiveness of classical guidance service program to increase students’ self-control. It used quantitative approach with quasi experiment using non equivalent pretest-posttest control group design. Subjects of the research were 80 students who were taken by cluster random sampling technique. They were divided into two groups, 40 students were in experimental group and 40 students were in control group. To collect data this research used interview guide and self-control scale. Data analysis technique which was used to test the effectiveness of classical guidance service program was Anacova analysis. The analysis result shows negative value 11.694 with coefficient t=4.259 and p+0.000. Based on research result it can be concluded that classical guidance services program was effective to increase students’ self-control. The results of this research are useful for guidance and counseling teachers to help students to increase self-control through classical guidance services program.